Table of Content - -, (Journal of Curriculum and Teaching Methodology, 2023)
Table of Content:1. Degree of embedding knowledge economy skills in the social studies courses for the primary stage in The Kingdom of Saudi ArabiaMrs. Mashael Saleh Al-Nefaie, Prof. Hanan Abdel Jalil Najmuldeen2. The Effectiveness of a Training Program Based on Professional Reflection in Developing the Active Learning Skills among Science Teachers in the Capital CityMrs. Nadia Mohamed Ahmed Mutahar, Co-Prof. Hazza Abdu Al-Homaidi3. The impact of artificial intelligence platforms on the e-learning environment in teaching the Arabic language to primary school studentsDr. Raad Jamal Al-Tlouhi4. The Extent to Which Twenty-First Century Skills Are Included in Digital Skills Books for the Fourth Grade of Primary School in The Kingdom of Saudi ArabiaMrs. Amani Muneer Alnufaei, Mrs. Ibtisam Ahmed Hakami , Prof. Najwa Atyan Almohammadi5. Productive Thinking Skills Included in Art Education Text Books for the Primary StageMrs. Hana Mohammed Al-Khasawneh, Prof. Ahmed Odeh Al-Qarra’a6. Evaluating the reality of the Islamic studies curriculum for the sixth grade of primary school in The Kingdom of Saudi Arabia in the light of pragmatic theoryMrs. Felwah Mohmmad Saqar Al-Wadany7. The Effectiveness of a linear Algebra Teaching Program based on the Graph Theory in Developing the Geometric Sense Skills among Mathematic Students at Faculty of Education Sana'aMrs. Afrah Abd Alrkeep Alsabri , Prof. Radman Mohamed Saeed
Keywords: Journal of Curriculum and Teaching Methodology